CLASSIFICATION OF OBJECTS ON FOUNDATION TENSOR MODELS - Мінаєв, Ю. М.; Вінник, Д. М.; Гайдай, А. В.; Апонасенко, Д. В.; Гончарова, Є. О. (Science-based technologies, 2009)
The questions of using the methods fuzzy and hierarchical clusterizations for object identifications, which mod-els are present in the manner of invariants of binary tensors. Software programs in the medium of MatLab, al-lowing execute a categorization of real objects (planes), is designed.